PENERAPAN MEDIA GAME SEMAI ANTI KORUPSI DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN AQIDAH AKHLAQ DI MI MIFTAHUL FALAH BANGKALAN - Mundiro Lailatul Muawaroh (IAIN Bone, 2020)
This reseach describe about the anti-corruption seedling game as a learning media in the subject of Aqeedah Akhlak. in this study the authors use. type of qualitative research. The results of this study are, first, to facilitate learning activities and collaboration between teachers and students. Students play an active role in learning activities using the game media anti-corruption seedlings. Students become disciplined by working well between groups, sharing information, reinforcing each other's arguments, and sharing ideas and ideas to get broad and accurate information. And students begin to understand the many moral values that must be possessed and must be applied in everyday life. Second, the teacher makes it easy to convey learning material for aqidah akhlaq, one of which is about instilling the moral values that students must have and the behaviors that must be instilled in students from an early age. In the anti-corruption semai media game there are 9 moral values that are learned by students and are expected to be applied in everyday life. By using the game media anti-corruption seedlings against students' understanding of the subject of aqidah akhlaq very much influence or benefit to students and make it easier for teachers to deliver learning material.Keyword : Aqidah Akhlak, Learning Media , Semai Games